Role of nucleoside/nucleotide analogues and low-dose hepatitis B immune globulin in prophylaxis of hepatitis B recurrence among cadaveric liver transplant recipients - Ajayi, Tokunbo; Luu, Harry; Saberi, Behnam; Hamilton, James P.; Konduk, Bugra Tolga; Özşeker, Burak; Al Khalloufi, Kawtar; Pustavoitau, Aliaksei; Philosophe, Benjamin; Cameron, Andrew M.; Gürakar, Ahmet (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Hepatitis B core antibody (HBcAb) positivity of the donor or the recipient may pose a risk of hepatitis B virus (HBV) reactivation following liver transplantation (LT). We retrospectively investigated patient survival and reactivation among recipients who were given low-dose Hepatitis B Immune Globulin (HBIG) plus antiviral agent (AV) versus AV only. Materials and Methods: Records of cadaveric LT recipients, between 2013 and 2016, with positive Hepatitis B surface Antigen (HBsAg) and/or HBcAb and recipients who had received LT from HBcAb-positive donors were reviewed. Patient characteristics and clinical data were extracted. Donor variables were retrieved from the United Network of Organ Sharing (UNOS) database. HBIG (1560 IU/mL) Intravenous (IV) was intraoperatively administered with three daily doses. Entecavir 1 mg daily was also given. STATA was used for statistical analysis. Results: There were 53 recipients; 39 (73.6%) were male with a median age of 59 y. HCV was the major indication in 30 (55.6%) patients. There were 28 recipients (52.8%) who received HBIG plus AV and 25 (47.2%) received AV only. The Model of End Stage Liver Disease (MELD) score between the groups were similar. Survival rates at 6, 12, and 24 months were 100% (n=53), 93.2% (n=44), and 100.0% (n=26), respectively. There was no reactivation; two recipients in the AV group and one in the HBIG plus AV group died within 12 months. Conclusion: This study supports the use of low-dose HBIG and AV for post-LT prophylaxis to be as effective as conventionally used high-dose HBIG (9600 IU) plus AV. Future prospective larger studies are warranted to examine the potential benefits of using AV alone without HBIG. Cite this article as: Ajayi T, Luu H, Saberi B, et al. Role of nucleoside/nucleotide analogues and low-dose hepatitis B immune globulin in prophylaxis of hepatitis B recurrence among cadaveric liver transplant recipients. Turk J Gastroenterol 2018; 29: 58-63.